Behavior of a DI Diesel Engine Fuelled with Blends of Waste Plastic Oil and Non Metallic Nano Additives - Sachuthananthan , B.; Vinoth , R.; Tamilselvan , N.; Fardeen , S. K.; Sai , P. Shanmuka (Research Aspects in Chemical and Materials Sciences Vol. 6, 2023)
The improvement of performance and decrease in emissions from a 4-stroke, single-cylinder diesel engine powered by Diesel-Waste Plastic Oil (WPO) obtained through pyrolysis process is discussed here. The Diesel-WPO blend and the nano additive were mixed using an ultrasonicator and a mechanical homogenizer. The Rice husk-based nanoadditives were mixed with WPO at concentrations of 25, 50, 75, and 100 ppm. The fuel mixture's stability was examined before it was employed in a diesel engine for performance and emission research. The results show that when compared to diesel, the W20 combination (20% WPO, 80% Diesel) indicated a 3.5% decrease in brake thermal efficiency (BTE) and an increase in brake-specific fuel consumption (BSFC) of 5.7%, at full load. When compared to Diesel, the W20NA75 blend's BTE increased by 2.6% and its fuel consumption decreased by 3.1% after the addition of Non Metallic Nano Additives (NA). When compared to diesel at maximum load, emissions such as hydrocarbon (HC), carbon monoxide (CO), and smoke opacity decreased by 15.3%, 7%, and 20.4%, respectively, while oxides of nitrogen (NOx) emission increased by 14.1%. It can be concluded that adding rice husk nanoparticles to W20 blend at a 75 ppm concentration helped CI engines run more efficiently and emit less pollutants. The inclusion of non-metallic nanoparticles to the WPO-diesel blend had a significant impact on the results, which also revealed a significant improvement in brake thermal efficiency.